HUBUNGAN ANTARA KEMAMPUAN MEMBACA DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SEKOLAH DASAR - Wahyuni Wahyuni; Siti Habsari Pratiwi; Nuril Husna (Prosiding Seminar Nasional USM, 2019)
The ability to read, especially in understanding the contents of reading is the spirit in solving mathematical problems. The inability of students to understand the contents of reading text makes students unable to solve mathematical problems given by the teacher. The study aims to describe the relationship between reading skills and mathematical problem solving abilities of elementary school students in Langsa City. This research is a descriptive qualitative study with the subject of grade 3 students at Seuriget City Langsa Elementary School, as many as 28 students. The results showed that students were less able to read the problem solving mathematical problem solving, especially in the first indicator, namely the ability to understand the problem. When students cannot understand the problems, students cannot plan problem solving, solving and making conclusions. So it can be concluded that there is a relationship between reading ability and mathematical problem solving ability of elementary school students in Langsa City.